2018
DOI: 10.1039/c7nj04661h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chalcogen atom variation in chalcogenadiazole fused indolo[2,3-a]carbazoles

Abstract: The chalcogen (O/S/Se)-induced intriguing variation of structural and optoelectronic properties in a series of chalcogenadiazole-fused indolo[2,3-a]carbazole donor–acceptor (D–A) molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[ 17,18 ] We have recently reported structure‐property relationship in oxadiazole‐, thiadiazole‐, and selenadiazole‐fused ICs. [ 19 ] Analogous di(furo/thieno/seleno‐pyrrolo)‐benzothiadiazole, [ 15,20–24 ] benzoselenadiazole, [ 20 ] and benzotriazole [ 25,26 ] have been synthesized using Cadogan cyclization [ 27 ] as a key step and incorporated into the conjugated copolymers, dyes, ladder conjugated polymers, [ 28 ] and non‐fullerene acceptors for organic photovoltaics. [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 17,18 ] We have recently reported structure‐property relationship in oxadiazole‐, thiadiazole‐, and selenadiazole‐fused ICs. [ 19 ] Analogous di(furo/thieno/seleno‐pyrrolo)‐benzothiadiazole, [ 15,20–24 ] benzoselenadiazole, [ 20 ] and benzotriazole [ 25,26 ] have been synthesized using Cadogan cyclization [ 27 ] as a key step and incorporated into the conjugated copolymers, dyes, ladder conjugated polymers, [ 28 ] and non‐fullerene acceptors for organic photovoltaics. [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Further, these Cadogan products were bisalkylated by treatment with DMF/NaOH and n‐butyl bromide to get compounds 13 a – c . This variety of chalcogens was found to show an efficient change in structural, optical as well as electrochemical properties [25] . The results revealed that 13 b was a better electron acceptor than 13 a and 13 c indicating the importance of oxygen with high electron affinity.…”
Section: Synthesis Of Chemical Frameworkmentioning
confidence: 94%
“…This variety of chalcogens was found to show an efficient change in structural, optical as well as electrochemical properties. [25] The results revealed that 13 b was a better electron acceptor than 13 a and 13 c indicating the importance of oxygen with high electron affinity. Furthermore, these experimental findings were supported by DFT calculations.…”
Section: Formation Of Carbazole Moietymentioning
confidence: 95%
See 1 more Smart Citation
“…and benzothiadiazole (Frizon et al, 2016). This change to more positive values, obtained due to the addition of a heavier chalcogen atom to the heterocycle, can be attributed to an increase in the electronegativity of the chalcogens and proved to be a relevant factor in determining the energies of HOMO and LUMO (Kawashima et al, 2015;Ghosh et al, 2018).…”
Section: Electrochemical Characterizationmentioning
confidence: 95%